Phase III randomized trial comparing 5-fluorouracil and oxaliplatin with or without docetaxel in first-line advanced gastric cancer chemotherapy (GASTFOX study). Issue 4 (April 2018) - Zaanan, Aziz; Samalin, Emmanuelle; Aparicio, Thomas; Bouche, Olivier; Laurent-Puig, Pierre; Manfredi, Sylvain; Michel, Pierre; Monterymard, Carole; Moreau, Marie; Rougier, Philippe; Tougeron, David; Taieb, Julien; et al.
Abstract: Introduction: In advanced gastric cancer, doublet regimen including platinum salts and fluoropyrimidine is considered as a standard first-line treatment. The addition of docetaxel (75 mg/m 2 q3w) to cisplatin (75 mg/m 2 q3w) and 5-fluorouracil has been shown to improve efficacy. However, this regimen (DCF) was associated with frequent severe toxicities (including more complicated neutropenia), limiting its use in clinical practice. Interesting alternative docetaxel-based regimens have been developed that need to be validated. Aim: GASTFOX study is a randomized phase III trial comparing FOLFOX alone or with docetaxel at 50 mg/m 2 (TFOX regimen) in first-line treatment for advanced gastric cancer. In both arms, cycle is repeated every 2 weeks until disease progression or unacceptable toxicity. Materials and methods: Main eligibility criteria: histologically proven locally advanced or metastatic gastric or esogastric junction adenocarcinoma, HER negative status, measurable disease, ECOG performance status 0 or 1, and adequate renal, hepatic and bone marrow functions. Results: The primary endpoint is radiological/clinical progression-free survival (PFS). A difference of 2 months for the median PFS in favor of TFOX is expected (HR = 0.73) Based on a two-sided α risk of 5% and a power of 90%, 454 events are required to show this difference. Secondary endpoints included overall survival, overall response rate, safety, quality of life and the therapeutic index. Conclusion: This study is planned to include 506 patients to demonstrate the superiority of TFOX over FOLFOX in first-line advanced gastric cancer treatment (NCT03006432).